ダイ 24 ジ ナンキョク チイキ カンソク タイ エットウ ホウコク 1983-1984 - 前, 晋爾; マエ, シンジ; Mae, Shinji (1990)
P(論文) 第24次南極地域観測越冬隊35名は1983年2月1日より昭和基地の運営を開始し, 1984年1月31日に終了した。この間昭和基地, みずほ基地を維持しつつ, 定常観測の他, 宙空系, 雪氷・地学系, 環境科学系による研究観測を実施した。研究観測では, IAGP(国際南極雪氷計画)の一環として「東クイーンモードランド地域雪氷・地学研究計画」(7年計画の2年次), MAP(中層大気国際共同観測計画)の一環としての「極域中層大気の総合観測」(4年計画の2年次), BIOMASS(南極海海洋生態系および海洋生物資源に関する生物学的研究計画)の一環としての「南極沿岸生態系における生物生産の基礎研究」(3年計画の2年次)が主たるプロジェクトであった。その他, 「環境モニタリング」と「ヒトの生理学的研究」を継続実施した。本報告では定常・研究観測の概要と設営部門の活動を記述する。 The wintering party of the 24th Japanese Antarctic Research Expedition consisting of 35 personnel carried out routine observations and research activities at Syowa and Mizuho Stations, along the coast of Lutzow-Holm Bay and in the area of East Queen Maud Land from January 1983 to January 1984. The main research activities at Syowa Station were coordinated observations of the polar middle atmosphere and marine biological production, which were performed as part of the International Middle Atmosphere Program (MAP) and the Biological Investigations of Marine Antarctic Systems and Stocks (BIOMASS). In addition to these activities at Syowa Station, survey trips for environmental research were carried out at short intervals along the coast of Lutzow-Holm Bay. Glaciological studies were carried out as part of the International Antarctic Glaciological Project (IAGP), at Mizuho Station and along the traverse routes to the Sor Rondane Mountains in East Queen Maud Land. The 411.1 m deep ice-core drilling was completed at Mizuho Station. departmental bulletin paper